2018
DOI: 10.1021/acs.jpcb.8b02500
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium Investigation on 2-Phenylethanol in Binary and Ternary Systems: Influence of High Pressure on Density and Solid–Liquid Phase Equilibrium

Abstract: Ionic liquids (ILs) are important new solvents proposed for applications in different separation processes. Herein, an idea of possible use of high pressure in a general strategy of production of 2-phenylethanol (PEA) is discussed. In this work, we present the influence of pressure on the density in binary systems of {1-hexyl-1-methylpyrrolidynium bis{(trifluoromethyl)sulfonyl}imide, [HMPYR][NTf], or 1-dodecyl-3-methylimidazolium bis{(trifluoromethyl)sulfonyl}imide, [DoMIM][NTf] + PEA} in a wide range of tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(95 reference statements)
1
3
1
Order By: Relevance
“…Figure shows the deviations of all of these published data from our data, including their expanded uncertainties at the 95% confidence level. It is clear that these existing density data do not agree with our data within their claimed mutual uncertainty, except for those of Domańska et al , and Lamas et al (up to 330 K). This is possibly due to impurities in the ionic liquid and/or the reported water content.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…Figure shows the deviations of all of these published data from our data, including their expanded uncertainties at the 95% confidence level. It is clear that these existing density data do not agree with our data within their claimed mutual uncertainty, except for those of Domańska et al , and Lamas et al (up to 330 K). This is possibly due to impurities in the ionic liquid and/or the reported water content.…”
Section: Resultscontrasting
confidence: 91%
“…Several authors have published results for the density of this ionic liquid as a function of temperature, all of which were determined by using the vibrating tube method (which was what was used in this study as well). Thus, we are able to compare our present data with those of Tariq et al, Tariq et al, Domańska and Wlazło, Lamas et al, Hazrati et al, Domańska et al, and Song et al, as shown in Figure .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…That is why a vast amount of experimental work has dealt with measurements of the SLE/LLE/VLE phase diagrams in ILs-based systems. The phase equilibria in systems that contain ILs has been the object of investigation in our group from many years [33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The SLE or LLE data provide a good tool for studying the thermodynamic behavior of many systems. Thus, many phase equilibria of infragrance materials have been measured by our group, for example, such as 2-phenylethanol, PEA (roses oil) [32][33][34][35]41,42].…”
Section: Introductionmentioning
confidence: 99%